METHOD OF THE CLUSTERING OF FRAGMENTS OF AERIAL PHOTOGRAPHS IN SPECTRAL-FREQUENCY SPACE - Бараннік, В.В.; Мусієнко, О. П.; Ялівець, К. С. (Science-based technologies, 2016)
In article the questions connected with onboard processing of aerial photographs which are received during the process of aero monitoring are considered. It is shown that aerial photographs are characterized by a different semantic saturation. Therefore during the processing of aerial photographs special attention needs to be paid to the choice of a semantic saturation and the most significant information about contours, borders of objects of the area. The choice of technology of processing of aerial photographs which can take the most key information from pictures is proved. Creation of classification of a semantic saturation of blocks of the image on the basis of dct-transformation, and also need of use of methods of the cluster analysis for a clustering of fragments of aerial photographs in spectral and frequency space is offered.